Ground-based observations of the VLF auroral hiss at Lovozero and Barentsburg observatories - Nikitenko A. S.; Kleimenova N. G.; Fedorenko Y. V.; Beketova E. B. (Solar-Terrestrial Physics)
The paper presents the results of the analysis of auroral hiss bursts, measured at Lovozero and Barentsburg observatories. These points are located on close geomagnetic meridians in the auroral and circumpolar zones. The auroral hiss bursts occur first in the auroral zone at Lovozero Observatory. Then, they fade out smoothly and occur in the circumpolar zone at Barentsburg Observatory. These events are observed when geomagnetic activity and the source of phase scintillation of GPS signals move from auroral to circumpolar latitudes. Analysis of magnetic field polarization and arrival angles of the bursts has shown that the area on the Earth surface, illuminated by hiss bursts, arose at auroral latitudes near Lovozero Observatory, and then moved to higher latitudes. Since propagation of the hiss to the ground and occurrence of GPS signal scintillation requires the presence of electron density irregularities of similar scales in the ionosphere, we assume that the same irregularities could cause both phenomena. A possible cause of their occurrence is the development of current-convective and (or) drift instability in the ionosphere caused by the development of field-aligned currents. Their development is indicated by the simultaneous recording of Pi1B pulsations. The results show that the termination of hiss at auroral latitudes may be caused by a shift of the geomagnetic disturbance region to high latitudes, rather than changes of wave propagation conditions in the ionosphere.